Hakikat dan Tujuan Filsafat Hukum Islam serta Relevansinya dalam Konteks Sosial Kontemporer - Muhammad Yasin; Achmad Musyahid; Fatmawati (CV Global Research Publication, 2026)
This study aims to analyze islamic legal philosophy as a conceptual framework that explains the nature, objectives, and relevance of islamic law in addressing the challenges of modern society. The research employs a library research method with a qualitative-descriptive and analytical approach through the examination of classical and contemporary literature on islamic law, legal theory (uṣūl al-fiqh), and maqāṣid al-sharī‘ah. The findings reveal that islamic legal philosophy is a reflective discipline integrating the ontological, epistemological, and axiological dimensions of islamic law. Its primary objectives are embodied in the concept of maqāṣid al-sharī‘ah, which seeks to protect religion, life, intellect, lineage, and property, while promoting public welfare and justice. The study further demonstrates that islamic legal philosophy remains highly relevant in responding to contemporary issues such as human rights, democracy, and digital technological development through adaptive and contextual ijtihād. Therefore, islamic legal philosophy may be positioned as a dynamic, rational, and future-oriented paradigm for legal development.